The role of social capital on the sustainability of MSMEs based in the City of Johannesburg, South Africa - Sibelekwana, Viwe (Graduate School of Business (GSB), 2024)
Due to the paucity in research on social competence and entrepreneurship on micro, small and medium enterprises (MSMEs), it has been argued that there is a need for scholarly work to be undertaken in order to comprehend how manifestations of social capital in small business communities can unlock effective government and broader institutional involvement followed by a re-think of development programmes. Against this background, the aim of this study was to assess the role of social capital when extending development initiatives, particularly, financial interventions aimed to develop MSMEs based in the City of Johannesburg, South Africa. Furthermore, the study sought to assess the impact of social capital on the financial sustainability of these MSMEs. Using a qualitative exploratory research approach, pre-defined criteria for participation was set and participation was purposively limited to a sample of 30 MSMEs based in the City of Johannesburg, South Africa. Four main themes emerged from data collected in this study, namely; social capital in particular socio-economic networks on MSME performance, social capital as an enabler of effective institutional support mechanism, impact of beneficial social capital on financial sustainability of MSMEs, and sustainability of livelihood strategies adopted by MSMEs. This study found that a significant number of the participating MSMEs were financially sustainable in the short-term. Furthermore, there was no deliberate financial support that was directed to these businesses by virtue of being associated to social clusters or formal opportunity structures. Beneficial social capital received by the participating MSMEs through their structural or relational social capital networks was mainly non-financial support and relates to improved access to information and market share through client referrals. The major concerning finding of this research study was that, should unforeseen events disrupt business operations of MSMEs in the City of Johannesburg, their livelihood would be severely impacted whether in the short or long-term as these businesses lack effective mitigation strategies to absorb shocks to maintain sustainable livelihood outcomes. Therefore, it is recommended that the Ministry of Small Business Development, in partnership with other role players develop and promote risk mitigating instruments to reduce the vulnerability context of these MSMEs to unknown future events that are likely to disrupt their livelihood outcomes and those of their families. Keywords: social capital, MSMEs, performance, sustainability, South Africa